2005
DOI: 10.3168/jds.s0022-0302(05)72839-3
|View full text |Cite
|
Sign up to set email alerts
|

An Iterative Sensory Procedure to Select Odor-Active Associations in Complex Consortia of Microorganisms: Application to the Construction of a Cheese Model

Abstract: The aim of this study was to develop and validate an iterative procedure based on odor assessment to select odor-active associations of microorganisms from a starting association of 82 strains (G1), which were chosen to be representative of Livarot cheese biodiversity. A 3-step dichotomous procedure was applied to reduce the starting association G1. At each step, 3 methods were used to evaluate the odor proximity between mother (n strains) and daughter (n/2 strains) associations: a direct assessment of odor di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…They utilize lactate and thus deacidify the cheese surface, enabling the establishment of less-acid-tolerant bacterial communities, which play a significant role in the quality and safety of the final product (79). To understand the BFIs that occur during ripening, Bonaiti et al (47) developed a microbial Livarot cheese model by selecting microbial associations contributing to cheese aroma. They succeeded in simplifying an ecosystem of 83 microbial strains from a commercial Livarot cheese to a subecosystem composed of nine species that had a strong similarity to that of the commercial cheese.…”
Section: Food Processingmentioning
confidence: 99%
“…They utilize lactate and thus deacidify the cheese surface, enabling the establishment of less-acid-tolerant bacterial communities, which play a significant role in the quality and safety of the final product (79). To understand the BFIs that occur during ripening, Bonaiti et al (47) developed a microbial Livarot cheese model by selecting microbial associations contributing to cheese aroma. They succeeded in simplifying an ecosystem of 83 microbial strains from a commercial Livarot cheese to a subecosystem composed of nine species that had a strong similarity to that of the commercial cheese.…”
Section: Food Processingmentioning
confidence: 99%
“…Some studies have revealed that yeasts transform sulfur amino acids into characteristic volatile sulfur compounds (VSC) that have a considerable impact on food flavor, notably in wine (Perpète et al , 2006) and cheese (Bonaïti et al , 2005). Sulfur metabolism has not been extensively studied in the hemiascomycete phylum, except in S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%
“…All these attributes contribute to defi ne cheese quality and safety and there is a need to understand how they are regulated. Bonaiti et al ( 2005 ) showed for the fi rst time an iterative procedure based on odour assessment to select odour-active associations of microorganisms in cheese microcosms. In order to study microbial interactions within a cheese microcosm further, they built model microbial communities generating odour comparable to that of Livarot cheese.…”
Section: Ripening: the Case Of Structure-function Relationships In Smmentioning
confidence: 99%
“…Iterative procedure for selection of odour-active microbial communities of microorganisms in cheese (Adapted fromBonaiti et al 2005 ). Selected daughter communities are shaded in blue (Color fi gure online)…”
mentioning
confidence: 99%